Access to Improved Seed for Small and Marginal Farmers in India: Emerging Challenges and Policy Support - Roy, Tuhin Narayan (International Journal of Economic Plants, 2015)
A survey experiment was conducted to access Improved Seed for Small and Marginal Farmers in India. The most vulnerable groups of the farming community in the India are marginal (less than one hectare of operational holding) and small (greater than one and less than two hectares of operational holding) farmers. Small and marginal farmers are the main contributors in Indian agriculture for food security and employment. Small and marginal holders have already recorded higher productivities compared to large sized holdings. They own 46.1% operational holding and contributes 51.2% to total crop output (GOI, 2011). But they are facing emerging challenges like population pressure, small holding, productivity, climate change, environment and resource degradation, infrastructure, input constraints, technology, post-harvest operations, trade, etc. Fragmentation to owners of small and marginal farms means higher costs for adopting modern technology and accessing production inputs and extension, credit and marketing services. Seeds are the important inputs for the productivity of crops. It is estimated that the direct contribution of quality seed alone to the total production is about 15–20% depending upon the crop and it can be further raised up to 45% with efficient management of other inputs. Only seed can be expected to respond to fertilizers and other inputs in a desired manner. In this regard, the role of policy in catering to the interest of various stakeholders as well as facilitating the overall growth of the sector becomes crucial.